A Motorcycle Safety System Design based on the Internet of Things - Annisaa Sri Indrawanti; Ridho Rahman Hariadi; Eka Prakarsa Mandyartha; Agung Mulyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
A huge number of motorbike thefts are still happening in Surabaya City. The most way the thief does to steal the motorbike is damaging the ignition lock using a